Levels and Health Risk of Pesticide Residues in Chinese Herbal Medicines - Wang, Ying; Gou, Yan; Zhang, Lei; Li, Chun; Wang, Zhao; Liu, Yuanxi; Geng, Zhao; Shen, Mingrui; Sun, Lei; Wei, Feng; Zhou, Juan; Gu, Lihong; et al. (Frontiers in Pharmacology, 2022)
In the present study, 168 pesticides in 1017 samples of 10 Chinese herbal medicines (CHMs) were simultaneously determined by high performance liquid (HPLC-MS/MS) and gas (GC-MS/MS) chromatography-tandem mass spectrometry. Totally 89.2% of the samples encompassed one or multiple pesticide residues, and residue concentrations in 60.5% of samples were less than 0.02 mg·kg-1, revealing the relatively low residue levels. The hazard quotient and hazard index methods were used to estimate the health risk for consumers. For more accurate risk assessment, the exposure frequency and exposure duration of CHMs were involved into the exposure assessment, which was obtained from a questionnaire data of 20917 volunteers. The results of chronic, acute and cumulative risk assessment indicated that consumption of CHMs is unlikely to pose a health risk to consumers. Ranking the risk of detected pesticides revealed phorate, BHC, triazophos, methidathion, terbufos and omethoate posed the highest risk. Our results also showed that pollution of the aboveground medicinal part was more serious. Although exposure to pesticides in tested CHMs was below dangerous levels, more strict controlled management should be carried out for banned pesticides due to the high detection rate and illegal use in actual planting practice.